Two polyphenol-rich Brazilian fruit extracts protect from diet-induced obesity and hepatic steatosis in mice. Issue 10 (22nd September 2020) - Ballard, Cíntia Reis; dos Santos, Elisvânia Freitas; Dubois, Marie-Julie; Pilon, Geneviève; Cazarin, Cinthia Baú Betim; Maróstica Junior, Mário Roberto; Marette, Andre
Abstract : Tucum-do-Pantanal and taruma-do-cerrado extracts, rich in polyphenols, improved metabolic health in mice. Abstract : Consumption of polyphenol-rich food is associated with better metabolic health. Tucum-do-Pantanal (Bactris setosa Mart) and taruma-do-cerrado (Vitex cymosa Bertero ex Spreng) are underexploited native Brazilian fruits with an important source of phytochemicals. In this study, we assessed the effects of 100 mg kg −1 tucum (TPE) and taruma (TCE) extracts on diet-induced obesity (DIO) C57BL/6J mice. After 8 weeks of daily treatment, TPE and TCE were found to significantly prevented the diet-induced body weight gain and fully protected against hepatic steatosis associated with a tendency to stimulate hepatic AMPK phosphorylation. TPE reduced visceral obesity and improved glucose metabolism as revealed by an improvement of the insulin tolerance test, a reduction in the insulin fasting level, and a decreased glucose-induced hyperinsulinemia during an oral glucose tolerance test. TPE and TCE showed promising effects on the treatment of obesity and NAFLD, furthermore, TPE on insulin resistance.